Park Street Church steeple, December 11, 1897 - Machado, Ernest M.A. (Tufts Archival Research Center, 2005)
View of the Park Street Church steeple. The dome of the Massachusetts State House, located on Beacon Street, is included in the background of the photograph. 6 13/16 x 4 9/16, 9 5/8 x 8 overall Albumen prints